PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP AKTIVITAS DAN PENGUASAAN MATERI OLEH SISWA - Dwi Cheri Lestari; tri jalmo; rini rita marpaung (Universitas Lampung, 2013)
Observations and interviewswithgrade eighth biology teacheratJunior High School7thBandarLampung, student learning outcomesare lowbecauseteachers uselearning modelsthat are less precise. This observation use to increase in student’s activitylearning andmastery of the materialthrough the application ofcooperative learning typeTGT’s model. The study designwasa non-equivalent pretestposttest. Samplesare first classVIIIaandVIIIbselectedby cluster randomsampling. The results showed thatstudents inall aspects ofthe activityobserved in theexperimental classesincreased.In the aspect ofvalue85.71%ask, answeraspectworth89.29%, and theaspects oftheir ideas/ opinionsworth86.90%. Mastery of the material also increased, withan averagevalueof 20pretest,posttestvaluesfor 60andN-gain of 0.09.Questionnairedatashowsthatall students(100%) felt happyandinterested incooperative learning modeltypeTGT. Key words :TGT, activities, students'mastery of the material.